2012
DOI: 10.1038/bcj.2011.50
|View full text |Cite
|
Sign up to set email alerts
|

Elevated calpain activity in acute myelogenous leukemia correlates with decreased calpastatin expression

Abstract: Calpains are intracellular cysteine proteases that have crucial roles in many physiological and pathological processes. Elevated calpain activity has been associated with many pathological states. Calpain inhibition can be protective or lethal depending on the context. Previous work has shown that c-myc transformation regulates calpain activity by suppressing calpastatin, the endogenous negative regulator of calpain. Here, we have investigated calpain activity in primary acute myelogenous leukemia (AML) blast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 60 publications
1
15
0
Order By: Relevance
“…A second feature of AML cells that would render them sensitive to glucopsychosine is the recent observation that calpain levels are significantly elevated while calpastatin, a calpain inhibitor, is significantly reduced in AML cells compared to normal hematopoietic cells [44].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A second feature of AML cells that would render them sensitive to glucopsychosine is the recent observation that calpain levels are significantly elevated while calpastatin, a calpain inhibitor, is significantly reduced in AML cells compared to normal hematopoietic cells [44].…”
Section: Discussionmentioning
confidence: 99%
“…This mode of death may be particularly important to a subset of AML patients, as it was recently shown that calpain levels in AML cells may be an important prognostic indicator. Niapour et al (2012) showed that patients samples with elevated cellular calpain levels had no response to PD150606 (a calpain inhibitor) whereas patient samples with low calpain levels were associated with improved complete response rates [44]. Thus, application of a stimulus to increase calpain in AML cells with already elevated calpain would be a novel approach at inducing a response in these patients, which do not respond to conventional therapy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations